2012
DOI: 10.1590/s0001-37652012005000052
|View full text |Cite
|
Sign up to set email alerts
|

Myenteric neuronal plasticity induced by Toxoplasma gondii (genotype III) on the duodenum of rats

Abstract: The effects of acute and chronic infection caused by Toxoplasma gondii on duodenal myenteric neurons were analyzed. Eighteen rats were assigned into four groups: Acute Control Group (ACG, n=4); Acute Experimental Group (AEG, n=4); Chronic Control Group (CCG, n=5); and Chronic Experimental Group (CEG, n=5). Rats from the AEG and CEG were inoculated orally with 105 genotype III (BTU-II strain) tachyzoites of T. gondii isolated from a dog with neurological signs. Acute groups were killed after 24 hours af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…These alterations seem to be related to several factors such as genotype strain, life form and inoculation route (oral or intraperitoneal) of the parasite in addition to the infection phase (acute or chronic), digestive tract region and the type of cells assessed [5][6][7][8][9][10][11][12][13][14][15] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These alterations seem to be related to several factors such as genotype strain, life form and inoculation route (oral or intraperitoneal) of the parasite in addition to the infection phase (acute or chronic), digestive tract region and the type of cells assessed [5][6][7][8][9][10][11][12][13][14][15] .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, components of the nervous system intrinsic to the digestive tract, the enteric nervous system (ENS), reveal signs of plasticity due to alterations induced by toxoplasmic infections in the intestinal wall. Therefore, available experimental studies carried out in rats [5][6][7][8][9][10][11][12][13][14][15] have shown that these plastic alterations depend on several factors such as strain; infectious stage (tachyzoites, bradyzoites, sporozoites) and inoculation route (oral or intraperitoneal) of the parasite; infection phase (acute or chronic) assessed; digestive tract region and group of nervous cells assessed. For instance, while chronic infection caused by tachyzoites from a genotype Ⅰ strain (for the SAG2 gene) causes atrophy of cell bodies in ileal myenteric neurons [7] , this same infection causes hypertrophy of cell bodies in colonic myenteric neurons [8] .…”
Section: Introductionmentioning
confidence: 99%
“…Toxoplasmosis is often a subclinical infection in both rats and humans, 12 which has also been observed in previous rat studies. [13][14][15][16] Our data showed that the infection did not cause neuronal loss in the general population (HuC/D þ) or nitrergic subpopulation (nNOS þ). T. gondii infection in rats after 30 days does not compromise the survival of myenteric neurons, regardless of the infective stage of the parasite that is used for the inoculation, which was also demonstrated in previous studies that evaluated the ileum (acute and chronic phase) and colon (chronic phase) in rats that were infected with tachyzoites.…”
Section: Discussionmentioning
confidence: 56%
“…Thus, NO modulates infectious responses that are caused by protozoa but can also induce quantitative and morphological changes in enteric neurons . In a previous study, no myenteric neuronal loss was observed in the duodenum in rats that were infected with tachyzoites (genotype III) for 24 hours and 30 days. A reduction of the number of myenteric neurons was observed in the jejunum and distal colon in rats 24 hours after infection with T. gondii oocysts (M7741 strain) …”
Section: Discussionmentioning
confidence: 87%